2016
DOI: 10.1371/journal.pone.0166270
|View full text |Cite
|
Sign up to set email alerts
|

Damage in the Multiethnic Malaysian Systemic Lupus Erythematosus (SLE) Cohort: Comparison with Other Cohorts Worldwide

Abstract: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease and despite the improvement in the survival in the past few decades, the morbidity due to disease damage remains significant. The objectives of this study were to investigate the disease damagepattern and determine the associated factors of damage in the multi-ethnic Malaysian SLE patients. We consecutively 424SLE patients who attended a consistent follow-up at the National University of Malaysia Medical Centre and Putrajaya Hospital were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 38 publications
10
48
1
Order By: Relevance
“…Majority of the patients in our cohort were less than 40 years old with mean age at diagnosis of 25.68 ± 11.58 years old. Nonetheless, our finding was similar with previous study [ 12 ] which included 80 SLE patients and the authors found no association between the SDI with age and age at diagnosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Majority of the patients in our cohort were less than 40 years old with mean age at diagnosis of 25.68 ± 11.58 years old. Nonetheless, our finding was similar with previous study [ 12 ] which included 80 SLE patients and the authors found no association between the SDI with age and age at diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of organ damage in our cohort was neuropsychiatric damage (18.1%) followed by musculoskeletal damage (12.8%) similar with past reports. [ 10 ] However, other reports [ 11 , 12 ] observed the commonest system affected was musculoskeletal with the most frequent complication being avascular necrosis followed by corticosteroid-induced osteoporosis. In addition, cutaneous lesion was the most frequent system affected found in Brazilian patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our LN patients had extra renal involvement with haematological manifestation being the commonest followed by musculoskeletal, cutaneous neurological and serositis and consistent with others. 18 As reported in the previous literature, we also demonstrated that high urine PCI, hypoalbuminaemia, C3 and C4 hypocomplementaemia, increased SLEDAI2K and SLICC-ACR were associated with disease activity. 13 Surprisingly, we found that ESR was not significantly different between patients with active and inactive LN.…”
Section: Discussionsupporting
confidence: 87%
“…Ethnic differences are known to account for the variability in disease susceptibility and expression in SLE [ 15 , 16 ]. The objectives of this study are to evaluate the pattern of damage and to identify the risk factors for accumulated damage in our group of childhood-onset SLE.…”
Section: Introductionmentioning
confidence: 99%